Creatio ex Omnibus: Pantheism and Its Values and Ethics - Mercury, Meg (Theology and science, 2024)
This paper refutes the common objection against pantheistic models of divinity that they are valueless or bereft of ethics due to the ambiguous model of God they espouse, arguing instead that pantheism can be construed as an inherently ethical model of divinity. It addresses common assumptions about omnibenevolent deities and the values they do or do not inspire. It then discusses the values that are arguably both immanent and inherent in nature itself. Finally, this paper makes the case that the ambiguity that pantheistic models of God acknowledge in nature is actually a necessary precondition for goodness itself.